2020
DOI: 10.1038/s41398-020-01091-y
|View full text |Cite
|
Sign up to set email alerts
|

Stress-related memories disrupt sociability and associated patterning of hippocampal activity: a role of hilar oxytocin receptor-positive interneurons

Abstract: In susceptible individuals, memories of stressful experiences can give rise to debilitating socio-affective symptoms. This occurs even when the ability to retrieve such memories is limited, as seen in patients suffering from traumatic amnesia. We therefore hypothesized that the encoding, rather than retrieval, mechanisms of stress-related memories underlie their impact on social and emotional behavior. To test this hypothesis, we used combinations of stress-enhanced and state-dependent fear conditioning, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 72 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…This increases OTR binding in networks like the lateral septum, where OT modulates the expression and extinction of socially derived threat responses in lactating females, which appears to be tempered by sex hormones ( Zoicas et al, 2014 ; Menon et al, 2018 ). In this brain area, OT signaling promotes rather exacerbated threat responses (freezing) and aggression responses to social threats ( Guzmán et al, 2013 ; Meyer et al, 2020 ), similarly, in the PVN of rodent females, increased OT release is correlated to high levels of maternal aggression ( Bosch et al, 2005 ). Excessive or uncontrollable socially induced stress is associated with OT signaling impairments, which are also correlated to high levels of anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This increases OTR binding in networks like the lateral septum, where OT modulates the expression and extinction of socially derived threat responses in lactating females, which appears to be tempered by sex hormones ( Zoicas et al, 2014 ; Menon et al, 2018 ). In this brain area, OT signaling promotes rather exacerbated threat responses (freezing) and aggression responses to social threats ( Guzmán et al, 2013 ; Meyer et al, 2020 ), similarly, in the PVN of rodent females, increased OT release is correlated to high levels of maternal aggression ( Bosch et al, 2005 ). Excessive or uncontrollable socially induced stress is associated with OT signaling impairments, which are also correlated to high levels of anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In the dentate gyrus (DG), OTRs are present almost exclusively in the region of hilus, where they are expressed by the GABAergic interneurons (INs) and, to a lesser extent, by the excitatory mossy cells ( Lin et al, 2017 ; Raam et al, 2017 ; Lin and Hsu, 2018 ; Meyer et al, 2020 ; Bertoni et al, 2021 ). GABAergic INs of the hilus constitute a neurochemically ( Lin et al, 2017 ; Raam et al, 2017 ; Meyer et al, 2020 ) and electrophysiologically ( Meyer et al, 2020 ) heterogeneous population: immunohistochemical studies have shown OTR expression in somatostatin- (SST + ), parvalbumin- (PV + ), calretinin- (CR + ), neuronal nitric oxide synthase- (nNOS + ), and neuropeptide Y-positive (NPY + ) GABAergic INs ( Lin et al, 2017 ; Raam et al, 2017 ; Meyer et al, 2020 ), but there is evidence for OTR expression even in parvalbumin- (PV – ) and cholecystokinin-negative (CCK – ) INs ( Harden and Frazier, 2016 ). In CA2/CA3 regions of the hippocampus, OTRs have been identified in both glutamatergic pyramidal cells (PYRs) and INs ( Lin et al, 2017 , 2018 ; Raam et al, 2017 ; Lin and Hsu, 2018 ; Tirko et al, 2018 ; Bertoni et al, 2021 ).…”
Section: Oxytocin Receptor Distribution In the Hippocampusmentioning
confidence: 99%
“…The dentate gyrus (DG) represents the main entry point of information into the hippocampus via perforant pathway as it is the first station of the hippocampal tri-synaptic circuit. The OTRs are mainly expressed in the GABAergic INs and the excitatory mossy cells in the hilum of the DG, whereas there has been no reported expression in the granular layer ( Lin et al, 2017 , 2018 ; Raam et al, 2017 ; Lin and Hsu, 2018 ; Meyer et al, 2020 ). Nevertheless, the electrophysiological effects of the OT on the neurons of this area remain poorly understood.…”
Section: Oxytocinergic Functional Modulation Of Specific Neurons Of T...mentioning
confidence: 99%
See 2 more Smart Citations